Origin of fast ion diffusion in super-ionic conductors - Xingfeng He (Nature Portfolio, 2017)
Ab initioatomistic modelling reveals that fast ion diffusion in super-ionic conductors is mediated by concerted migration of multiple ions. On the basis of this understanding, a universal strategy for designing fast ion conductors is proposed and demonstrated.